2019
DOI: 10.1039/c9pp00148d
|View full text |Cite
|
Sign up to set email alerts
|

The Paternò–Büchi reaction –a comprehensive review

Abstract: This review represents the most complete description of the scientific results obtained on a photochemical reaction described 110 years ago by an Italian scientist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 581 publications
1
67
0
Order By: Relevance
“… 3 Similarly, excitation of a carbonyl compound in the presence of an alkene can result in a [2 + 2] photocycloaddition reaction to provide an oxetane as product, known as the Paternò–Büchi reaction. 4 In contrast, the corresponding aza Paternò–Büchi reaction, in which an imine and alkene compound react under photochemical conditions to form an azetidine, is far less developed. Azetidines exist in numerous natural products ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Similarly, excitation of a carbonyl compound in the presence of an alkene can result in a [2 + 2] photocycloaddition reaction to provide an oxetane as product, known as the Paternò–Büchi reaction. 4 In contrast, the corresponding aza Paternò–Büchi reaction, in which an imine and alkene compound react under photochemical conditions to form an azetidine, is far less developed. Azetidines exist in numerous natural products ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed us to immediately eliminate unreactive substrates such as aliphatic oximes (16) photocycloadditions, the reactivity of excited state glyoxylate oximes has not yet been investigated. 15 After irradiation of 14 with blue LED lights in the presence of 1-hexene and 2.5 mol% 11•PF6, we were able to isolate the desired azetidine product (15) in 69% yield. Evaluation of several commercially available photocatalysts revealed that the reaction efficiency significantly decreases with photocatalysts that have a triplet energy (ET) below 60 kcal mol -1 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…13,14 However, this approach is currently only used to access oxetane and cyclobutane scaffolds from a corresponding excited state carbonyl or alkene, highlighting that the synthesis of azetidines via photochemical [2+2] cycloadditions, also referred to as aza Paternò-Büchi reactions, remains a challenge. [15][16] Only a small number of imines are known to undergo intermolecular aza Paternò-Büchi reactions, mostly relying on imines such as isoindolones or azauracils, which provide photocycloadducts with limited synthetic utility (1-3) ( Fig. 1A).…”
Section: Underdeveloped Herein We Report a Visible Light-mediated Inmentioning
confidence: 99%
“…Finally, Paternò-Büchi photochemical reaction 79 of alkenyl boronates and benzophenone was also developed by D'Annibale and co-workers. 80 Irradiation of alkenyl boronate 82 in the presence of benzophenone in benzene at 310 nm led to oxetane 83 (Scheme 37), whereas the corresponding MIDA esters gave acyclic tertiary alcohols originating from allylic hydrogen abstraction by triplet benzophenone and coupling of the radicals thus obtained.…”
Section: Short Review Synthesis Scheme 36 Enantioselective Intermolecmentioning
confidence: 99%